Modal Sosial dan Pemberdayaan Masyarakat dalam Perspektif Ekonomi Islam - Andriano, Beni; Yunisva Aviva, Itsla (AL-IBNOR, 2025)
Social capital and community empowerment are two interrelated concepts in achieving sustainable social and economic progress. In the perspective of Islamic Economics, these two concepts not only focus on material well-being, but also on achieving higher life goals based on sharia principles. This article discusses the importance of social capital in community empowerment and how the values ​​of Islamic Economics, such as justice, solidarity, and the principles of fair distribution of wealth, can strengthen social capital and encourage sustainable empowerment. Using a qualitative approach, this article explores community empowerment mechanisms that can be optimized through Islamic values ​​that prioritize justice, mutual assistance and sustainability.